Knockout of the Gsta4 Gene in Male Mice Leads to an Altered Pattern of Hepatic Protein Carbonylation and Enhanced Inflammation Following Chronic Consumption of an Ethanol Diet. (30th May 2018) - Shearn, Colin T.; Pulliam, Casey F.; Pedersen, Kim; Meredith, Kyle; Mercer, Kelly E.; Saba, Laura M.; Orlicky, David J.; Ronis, Martin J.; Petersen, Dennis R.
Abstract : Background: Glutathione S‐transferase A4‐4 (GSTA4) is a key enzyme for removal of toxic lipid peroxidation products such as 4‐hydroxynonenal (4‐HNE). In this study, we examined the potential role of GSTA4 on protein carbonylation and progression of alcoholic liver disease by examining the development of liver injury in male wild‐type (WT) SV/J mice and SV/J mice lacking functional GSTA4 (GSTA4 −/− mice). Methods: Adult male WT and GSTA4 −/− mice were fed chow ( N = 10 to 12) or high‐fat Lieber‐DeCarli liquid diets containing up to 28% calories as ethanol (EtOH) ( N = 18 to 20) for 116 days. At the end of the study, half of the EtOH‐fed mice were acutely challenged with an EtOH binge (3 g/kg given intragastrically) 12 hours before sacrifice. Carbonylation of liver proteins was assessed by immunohistochemical staining for 4‐HNE adduction and by comprehensive liquid chromatography–tandem mass spectrometry (LC‐MS/MS) of purified carbonylated proteins. Results: Chronic EtOH intake significantly increased hepatic 4‐HNE adduction and protein carbonylation, including carbonylation of ribosomal proteins. EtOH intake also resulted in steatosis and increased serum alanine aminotransferase. Hepatic infiltration with B cells, T cells, and neutrophils and mRNA expression of pro‐inflammatory cytokines tumor necrosis factor (TNF) α and interferon (IFN) γ was modest in WT mice. However, an EtOH binge increased hepatic necrosis, hepatic cell proliferation, and expression of TNF α mRNA ( p < 0.05). EtOH treatment of GSTA4 −/− mice increased B‐cell infiltration and increased mRNA expression of TNF α and IFN γ and of matrix remodeling markers MMP9, MMP13, and Col1A1 ( p < 0.05). GSTA4 −/− mice exhibited panlobular rather than periportal distribution of 4‐HNE‐adducted proteins and increased overall 4‐HNE staining after EtOH binge. Comprehensive LC‐MS of carbonylated proteins identified 1, 022 proteins of which 189 were unique to the GSTA4 −/− group. Conclusions: These data suggest long‐term adaptation to EtOH in WT mice does not occur in GSTA4 −/− mice. Products of lipid peroxidation appear to play a role in inflammatory responses due to EtOH. And EtOH effects on B‐cell infiltration and autoimmune responses may be secondary to formation of carbonyl adducts. Abstract : Chronic EtOH consumption results in a periportal accumulation (PT) of proteins that are post‐translationally modified by 4‐Hydroxy‐2‐nonenal. Using mice that lack expression of the 4‐Hydroxy‐2‐nonenal metabolizing enzyme GSTA4‐4, research herein provides evidence that GSTA4‐4 is critical in mitigating the accumulation of 4‐HNE modified proteins and therefore oxidative injury within the centrilobular region (CV) during chronic ethanol consumption.